BUSINESS EDUCATORS’ PERCEPTIONS OF THE CHALLENGES AND PROSPECTS OF INTEGRATING ARTIFICIAL INTELLIGENCE IN VOCATIONAL AND TECHNICAL EDUCATION IN UNIVERSITIES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2026)
The study examined Business educators’ perceptions of the challenges and prospects of integrating Artificial Intelligence (AI) in Vocational and Technical Education (VTE) in Universities in Anambra State. Two research questions guided the study. Descriptive survey research design was adopted in carrying out the study. The area of the study was limited to Anambra State. All the 35 Business Educators from the universities in Anambra State were used for the study. Instrument for data collection was a structured questionnaire. The instrument was validated by three experts. The reliability of the instrument was ascertained using Cronbach Alpha reliability technique which yielded an overall coefficient of 0.90. Data collected were analyzed using mean and standard deviation. Results revealed that the challenges to AI integration include lack of adequate knowledge of AI concepts and tools, limited access to AI-enabled teaching resources in most VTE institutions, lack of institutional policy and strategic framework for integrating AI into the curriculum, among others. The study also revealed that prospects of integrating AI into VTE as identified by business educators include that it can make teaching and learning more efficient and personalized, enhance students’ access to learning resources, foster collaboration and knowledge sharing among educators and students, among others. Based on the findings, the study recommended among others that Federal and State Ministries of Education, in collaboration with teacher training institutions and professional associations such as ABEN, should organize continuous capacity-building programmes on AI literacy and application for business educators. This will improve their digital competence and confidence in using AI tools for instructional purposes.
Keywords: Business educators; Artificial Intelligence (AI); Vocational and Technical Education; Business Education